Fitness-to-drive for glioblastoma patients: Guidance from the Swiss Neuro-Oncology Society (SwissNOS) and the Swiss Society for Legal Medicine (SGRM) - Hofer, Silvia; Keller, Kristina; Imbach, Lukas; Roelcke, Ulrich; Hutter, Gregor; Hundsberger, Thomas; Hertler, Caroline; Le Rhun, Emilie; Vasella, Flavio; Cordier, Dominik; Neidert, Marian; Hottinger, Andreas; et al. (Swiss medical weekly, 2021)
OBJECTIVE The management of brain tumour patients who would like to resume driving is complex, and needs multidisciplinary input and a consensus among treating physicians. The Swiss Neuro-Oncology Society (SwissNOS) and the Swiss Society for Legal Medicine (SGRM) aim to provide guidance on how to assess “fitness-to-drive” of glioblastoma patients and to harmonise the relevant procedures in Switzerland. METHODS At several meetings, Swiss neuro-oncologists discussed common practices on how to advise patients with a stable, i.e., non-progressive, glioblastoma, who wish to resume driving after the initial standard tumour treatment. All participants of the SwissNOS meetings were invited twice to return a questionnaire (modified Delphi process) on specific tools/procedures they commonly use to assess “fitness-to-drive” of their patients. Answers were analysed to formulate a tentative consensus for a structured and reasonable approach. RESULTS Consensus on minimum requirements for a “fitness-to-drive”programme for glioblastoma patients could be reached among Swiss neuro-oncologists. The recommendations were based on existing guidelines and expert opinions regarding patients with seizures, visual disturbances, cognitive impairment or focal deficits for safe driving. At this point in time, the Swiss neuro-oncologists agreed on the following requirements for glioblastoma patients after the initial standard therapy and without a seizure for at least 12 months: (1) stable cranial magnetic resonance imaging (MRI) according to Response Assessment in Neuro-Oncology (RANO) criteria, to be repeated every 3 months; (2) thorough medical history, including current or new medication, a comprehensive neurological examination at baseline (T0) and every 3 months thereafter, optionally an electrocencephalogram (EEG) at baseline; (3) ophthalmological examination including visual acuity and intact visual fields; and (4) optional neuropsychological assessment with a focus on safe driving. Test results have to be compatible with safe driving at any time-point. Patients should be informed about test results and optionally sign a document. CONCLUSIONS We propose regular thorough clinical neurological examination and brain MRI, optional EEG, neuropsychological and visual assessments to confirm “fitness-to-drive” for glioblastoma patients after initial tumour-directed therapy. The proposed “fitness-to-drive” assessments for glioblastoma patients serves as the basis for a prospective Swiss Pilot Project GLIODRIVE (BASEC ProjectID 2020-00365) to test feasibility, adherence and safety in a structured manner for patients who wish to resume driving. Research will focus on confirming the usefulness of the proposed tools in predicting “fitness-to-drive” and match results with events obtained from the road traffic registry (Strassenverkehrsamt).